Analysis of Lead (Pb) Metal Content in Catfish Meat (Clarias batrachus L) Sold at Bekonang Market, Sukoharjo - Jamilatun, Makhabbah; Agustin, Wiwit Widitya; Tolkhah, Ronald (Formosa Journal of Science and Technology, 2024)
Catfish (Clarias bathracus L) can survive and be able to tolerate polluted water conditions. Lead metal naturally occurs in water and contaminates the organisms in it. Lead metal contamination in fish will cause poisoning and brain damage if it enters the human body's metabolism and accumulates in amounts that exceed the threshold. This research was conducted to determine the content of Pb metal in catfish meat sold at Bekonang Market, Sukoharjo. The method used in this research is a qualitative analysis using the K2CrO4 reagent and a quantitative analysis using Atomic Absorption Spectrophotometry. The results of the research with K2CrO4 reagent showed that samples A, B, C, D, and E were negative respectively. The average levels of lead (Pb) in catfish meat samples A, B, C, D, and E were -21.98 mg/Kg ± 0.140; -22.10 mg/Kg ± 0.035; -24.32 mg/Kg ± 0.107; -10.99 mg/Kg ± 0.191; and -24.36 mg/Kg ± 0.091. Based on the results of the study, it can be concluded that the content is still below the threshold according to the requirements for lead (Pb) levels allowed by Republic of Indonesia Food and Drug Supervisory Agency Regulation Number 5 of 2018 concerning the Maximum Limit of Heavy Metal Contamination of 20 mg/kg.